Perinatal Asphyxia in Preterm Neonates Leads to Serum Changes in Protein S-100 and Neuron Specific Enolase - Giuseppe, Distefano; Sergio, Curreri; Pasqua, Betta; Giovanni, Li V.; Salvatore, Cilauro; Frigiola, Alessandro; Petra, Huppi; Maurizio, Amato (Current Neurovascular Research, 2009)
In preterm infants, neurological signs and clinical manifestations of brain damage are limited criteria for diagnosis of neurologic sequelae. Early indicators of brain damage are needed and currently some specific biochemical markers of brain injury are investigated to assess regional brain damage after perinatal asphyxia in neonates. In this study Protein S-100 (PS-100) and Neuron Specific Enolase (NSE) serum levels were studied serially during the perinatal period in preterm neonates with perinatal asphyxia as markers of glial and neuronal damage respectively. Thirty outborn preterm infants with perinatal asphyxia were studied at 3, 24, 48 hours and 7 days of life. According to Apgar scores at 1' and cord blood pH and lacticidemia (LA), patients were divided in two groups: 15 of them (GA 33±1.2 wk, BW 1790±383 g) with severe asphyxia (Apgar <4, pH7.0±0.08, LA 6.29±0.79 mM/L) and 15 (GA 32±1.8 wk, BW 1810±290 g) with mild asphyxia (Apgar between 4-6, pH 7.18±0.05, LA 2.59±0.61 mM/L). Ten gestational age matched healthy preterm neonates were studied as control group. Cerebral ultrasound examinations (7 MHz) were performed at birth and repeated at 3 weeks of life. The results of this study show that neonates with severe asphyxia at any time had significantly more elevated mean serum levels of both markers compared to the group with mild asphyxia and to the control group (p<0.05). The values of control group were also significantly lower in comparison with that of mild asphyxia. In neonates with severe asphyxia, NSE values decreased constantly from birth to the seventh day of life, while PS-100 showed a different pattern increasing progressively between 3 h and 7 days. In neonates with mild asphyxia serum values of both markers showed decreasing levels through the study period. The results of this study suggest that perinatal asphyxia is associated with the release of different brain cellular proteins in the blood of preterm infants with different time course indicating specific regional cellular injury. The more elevated levels of NSE at birth found in the newborns with severe asphyxia could be considered as an early biomarker of neuronal necrotic damage in the ischaemic phase of perinatal cerebral hypoxic-ischaemic insult; progressive increase of PS-100 during the first week of life in the same neonates could be expression of apoptotic damage of glial cells occurring in the reperfusion phase of cerebral ischaemia.
Keywords: regional brain lesions